Implementation Of Physical Fitness Test Measurements For Pencak Silat Sport Branch Using An Application - Hidayat, Thawfiq; Hartati, Hartati; Destriana, Destriana (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2024)
The study, titled "Implementation of Physical Fitness Test Measurement for Pencak Silat Sport Using an Application for Students at Palembang 03 Public Junior High School," aims to establish normative categories for assessing physical fitness test results in pencak silat using an application. The physical test components include strength, muscle power, flexibility, balance, endurance, speed, and agility tests. This research follows a quantitative approach with a descriptive research design. The participants consist of 30 pencak silat extracurricular students at Palembang 03 Public Junior High School, comprising 13 male students and 7 female students. Data were collected through various tests, utilizing instruments such as the bleep test for endurance, a 30-meter sprint for speed, the agility t-test for agility, 1-minute push-ups for arm strength, vertical jump for muscle explosive power, and the standing stroke test for balance. The research took place at S Palembang 03 Public Junior High School in collaboration with a member of Mgmp Pjok Palembang City. The findings indicate that the average physical condition of extracurricular pencak silat students at Palembang 03 Public Junior High School falls within the very good category (10.8%), good category (21.6%), fair category (41.6%), less than percentage category (12.5%), and very less than percentage category (13.3%). In conclusion, the overall physical condition of extracurricular students is in the fair category with a percentage of (41.6%). The intention of this research is to promote awareness among students to continually enhance and maintain their physical condition for achieving maximum success.